PENDAMPINGAN KOMUNIKASI PEMASARAN KEDAI KOPI JEVERA COFFEE AND EATERY CIKARANG - Shihab, Mohammad; Perdana, Abhirama SD (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
Indonesia is the world's third-largest coffee producer in 2022/2023. Moreover, the domestic coffee consumption trend has been steadily increasing over the last five years. It is no wonder that the coffee shop industry in Indonesia has been experiencing rapid development in recent years. As a result, the competition among coffee shops has become increasingly fierce, necessitating coffee shops to have marketing communication strategies to build brand awareness and capture consumers. Hence, support activities have been carried out to assist in the marketing communication of Jevera Coffee and Eatery in Cikarang, Bekasi Regency, West Java. The support was provided for 30 days with two main activities, namely, social media management and brand activation. The evaluation results have shown that brand activation through special events can help increase the number of sales transactions in this coffee shop. Additionally, social media monitoring indicates that the shared content has generated an online interaction rate of 1.8%. Consumers are eagerly anticipating special events organized at Jevera Coffee and Eatery. References Annur, C. M. (2020, November 24). Konsumsi Kopi Domestik di Indonesia Terus Meningkat selama 5 Tahun Terakhir. Diambil kembali dari Databoks: https://databoks.katadata.co.id/datapublish/2020/11/24/konsumsi-kopi-domestik-di-indonesia-terus-meningkat-selama-5-tahun-terakhir As'ad, M. H., & Aji, J. M. (2020). Faktor Yang Mempengaruhi Preferensi Konsumen Kedai Kopi Modern Di Bondowoso. Jurnal Sosial Ekonomi Pertanian, 182-199. Diambil kembali dari https://jurnal.unej.ac.id/index.php/JSEP/article/view/16441/8459 Fransisca, M., Hartanto, D. D., & Sylvia, M. (2020). Perancangan Brand Activation Excelso Jemursari pada Masa Pandemi Covid-19. Jurnal DKV Adiwarna, Vol. 1(16), 1-11. Diambil kembali dari https://publication.petra.ac.id/index.php/dkv/article/view/10425/9303 HP, A., Handayani, Y. I., & Ramadhanti, D. N. (2022). Meningkatkan Penjualan Produk UMKM Di Desa Pugerwetan Melalui Kanal Media Sosial Dan Online Marketplace. Jurnal Abdi Panca Marga, Vol. 3(2), 98-102. doi:10.51747/abdipancamarga.v3i2.1143 Muhamad, N. (2023, Juli 6). Indonesia Jadi Produsen Kopi Terbesar Ketiga di Dunia pada 2022/2023. Diambil kembali dari Databoks; https://databoks.katadata.co.id/datapublish/2023/07/06/indonesia-jadi-produsen-kopi-terbesar-ketiga-di-dunia-pada-20222023 Zakiyah, N. N., Gunawan, G., & Romadi, U. (2022). Pengaruh Media Sosial Instragram Terhadap Keputusan Berkunjung di Kopi Taji Lereng Bromo. Jurnal Sains Komunikasi Dan Pengembangan Masyarakat, 145-156. doi:10.29244/jskpm.v6i1.970